Social identity and social exchange: identification, support, and withdrawal from the job - van Knippenberg, D.; van Dick, R.; Tavares, S. (Journal of Applied Social Psychology, 2007)
Integrating insights from the social exchange perspective and the social identity perspective, we propose that evaluations of support received from the organization and its representatives and organizational identification interact to predict withdrawal from the job. The relationship of support with withdrawal is proposed to be weaker the more strongly employees identify with the organization. This prediction was confirmed in 2 samples focusing on different operationalizations of support and withdrawal. Study 1 explored the interaction between organizational support and organizational identification in predicting turnover intention; Study 2 investigated the link between supervisor support and organizational identification and absenteeism. The present study thus yields evidence that may lay the groundwork for further integration of social exchange and social identity analyses of organizational behavior